2024
DOI: 10.3389/fimmu.2024.1335911
|View full text |Cite
|
Sign up to set email alerts
|

The α-Gal epitope - the cause of a global allergic disease

Marija Perusko,
Jeanette Grundström,
Maria Eldh
et al.

Abstract: The galactose-α-1,3-galactose (α-Gal) epitope is the cause of a global allergic disease, the α-Gal syndrome (AGS). It is a severe form of allergy to food and products of mammalian origin where IgE against the mammalian carbohydrate, α-Gal, is the cause of the allergic reactions. Allergic reactions triggered by parenterally administered α-Gal sources appear immediately, but those triggered via the oral route appear with a latency of several hours. The α-Gal epitope is highly immunogenic to humans, apes and old-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 173 publications
0
2
0
Order By: Relevance
“…35 Of note, tandem mass spectrometry (MS/MS) and antibody staining showed that mouse LRP1 N-glycans exhibit the terminal Galα1-3Galβ1-4GlcNAc (α-Gal) epitope (Figures 4B and S6), a unique carbohydrate antigen abundantly expressed on glycoconjugates of most mammals yet absent in humans. 36, 37 To determine which of these N-glycan structures are ligand(s) for hDCIR and mDCIR1, we performed an enzyme-linked lectin assay using neo-glycoproteins generated by covalent coupling of biantennary complex-type N-glycans with either terminal GlcNAc, Gal, α-Gal or α2,6-linked sialic residues to bovine serum albumin (BSA). We found that both hDCIR-ECD and mDCIR1-ECD strongly interact with biantennary complex-type N-glycans with terminal galactose residues, including those carrying the α-Gal epitope, but poorly or not at all with agalactosylated or sialylated N-glycans (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Of note, tandem mass spectrometry (MS/MS) and antibody staining showed that mouse LRP1 N-glycans exhibit the terminal Galα1-3Galβ1-4GlcNAc (α-Gal) epitope (Figures 4B and S6), a unique carbohydrate antigen abundantly expressed on glycoconjugates of most mammals yet absent in humans. 36, 37 To determine which of these N-glycan structures are ligand(s) for hDCIR and mDCIR1, we performed an enzyme-linked lectin assay using neo-glycoproteins generated by covalent coupling of biantennary complex-type N-glycans with either terminal GlcNAc, Gal, α-Gal or α2,6-linked sialic residues to bovine serum albumin (BSA). We found that both hDCIR-ECD and mDCIR1-ECD strongly interact with biantennary complex-type N-glycans with terminal galactose residues, including those carrying the α-Gal epitope, but poorly or not at all with agalactosylated or sialylated N-glycans (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…alphagal syndrome, and hypersensitivity reactions to cetuximab, a chimeric mouse-human monoclonal antibody used to treat cancers of the bowel and neck. 36,37,[65][66][67] To our knowledge, hDCIR is the first human lectin described as interacting with the a-Gal epitope carried on glycoproteins, suggesting that this lectin may play an important role in a-Gal-mediated diseases. In agreement with this idea, a recent study established that DCIR on the surface of mast cells mediates the recognition and uptake of cockroach allergen, which contains the a-Gal epitope on N-glycans, and enhances cockroach/IgE-induced mast cell activation and atopic dermatitis-like inflammation.…”
Section: Discussionmentioning
confidence: 99%